Do Scholarships Help Students Continue Their Education? - World Bank (World Bank, Washington, DC, 2012)
The World Bank is committed to assisting developing countries raise their educational standards, part of the United Nations millennium development goals. The work includes supporting projects that explore how best to support children staying in school. One recent project was in Cambodia, where boys and girls from poor families were offered scholarships if they continued beyond primary school. The project's evaluation, which ran over two school years, showed that scholarships worked as a way of getting children to stay in school. But it also found that children who were offered scholarships did not do measurably better on vocabulary or math tests than peers who were not offered scholarships-despite the fact that the former group had higher enrollments and attendance. Cambodia has had numerous scholarship programs funded by the government and outside donors. One project, funded by the Japan fund for poverty reduction, tried to keep girls in school by giving their families annual cash 'scholarships'-which could be used for any purpose- during the first three years of secondary school. The project covered the 2003- 2006 school years and raised school attendance rates by 20 to 30 percentage points. Building on that experience, a government program supported by the World Bank's Cambodia education sector support project was launched in such a way as to test the optimal scholarship amount and measure the effect on both boys and girls.